2017
DOI: 10.1016/j.jpeds.2017.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of the Pediatric Emergency Department in Reducing Unintended Adolescent Pregnancy

Abstract: Objectives To determine pregnancy risk and receptiveness to emergency department (ED)-based pregnancy prevention interventions among adolescents accessing care in the ED. Study design Cross-sectional electronic survey of adolescent females in a pediatric ED used to calculate the pregnancy risk index (PRI), a validated measure estimating the annual risk of becoming pregnant based upon recent sexual activity, contraceptive method(s), and method-specific contraceptive failure rates) and interest in receipt of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Since the ED visit may be the only contact with a medical clinician for many adolescents, EDs represent a key site for STI prevention and treatment. However, while adolescent patients and their parents have repeatedly demonstrated acceptance of sexual health discussion and HIV/STI testing, clinicians have reported less acceptance of directly providing this care . Further, racial disparities have been demonstrated in ED‐based STI testing, with black females nearly four times more likely to be tested than nonblack females .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the ED visit may be the only contact with a medical clinician for many adolescents, EDs represent a key site for STI prevention and treatment. However, while adolescent patients and their parents have repeatedly demonstrated acceptance of sexual health discussion and HIV/STI testing, clinicians have reported less acceptance of directly providing this care . Further, racial disparities have been demonstrated in ED‐based STI testing, with black females nearly four times more likely to be tested than nonblack females .…”
Section: Discussionmentioning
confidence: 99%
“…Despite declines in adolescent pregnancy rates over the past several decades, the United States has one of the highest rates in the industrialized world, and reduction of adolescent pregnancy remains a top priority for both the CDC and the U.S. Department of Health and Human Services . The risk of unintended pregnancy among adolescent females seeking care in the pediatric ED setting is more than three times greater than the national average . Frequent ED utilization and lacking a primary provider or private insurance are associated with higher risk for unintended pregnancy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study conducted in an urban PED, nearly one‐third of adolescent females ages 15 to 19 were either pregnant or at high risk of becoming pregnant in the next year . Studies have also shown that adolescent females seeking care in the PED would welcome contraception counseling at the time of the PED visit . However, it is unclear if contraceptive counseling in the PED is an effective mechanism for increasing contraception initiation.…”
mentioning
confidence: 86%